The Jibril Method Implementasi Metode Jibril sebagai Upaya Memperbaiki Pelafalan Huruf-Huruf Hijaiyah dalam Konteks Membaca Al-Qur’an di Kelas 5 dan 6 MDA Al-Hidayah Desa Cikopo - Diki Muhammad Abdillah; Dyah Wulandari (Jurnal Pengabdian kepada Masyarakat Bina Darma, 2022)
This study aims to improve the pronunciation of the hijaiyah letters of the students when reading the Qur'an by using the Jibril method as a learning method. This study used a Participatory Action Research (PAR) design. The subjects in this study were students in grades 5 and 6 of MDA Al-Hidayah, Cikopo Village, totaling 11 people. First, the researcher conducted pre-action observations to determine the students' ability to pronounce the observed hijaiyah letters. Secondresearchers carry out actions in the form of implementing learning using the Jibril method. The implementation of actions in each cycle includes planning activities, implementing actions, carrying out observations, evaluations and reflections in accordance with the initial planning. Researchers used two cycles through post-test and reflection at the end of each cycle.The result of this study is that in the end the students were able to improve the pronunciation of the hijaiyah letters well. So that the Jibril method is a learning method that can improve the students' ability to pronounce the hijaiyah letters when reading the Qur'an.